Parametric study on the rotation capacity of stiffened end-plate beam-to-column connection - Ostrowski, Krzysztof; Kozłowski, Aleksander (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Rotation capacity is one of the joint parameters needed to be taken into account of the real joint behaviour in a global analysis. It has a special influence on the plastic design of steel frames. The results of the parametric study of the stiffened bolted end-plate beam-to-column connection have been presented in the paper. The main investigated parameters are: thickness of end plate “tp”, horizontal bolt spacing “w” and distance of the bolt to plate edge “cg1”. The analysis was performed with the use of finite element method, based on the numerical experiment plan.